2016
DOI: 10.1016/j.watres.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for stabilizing fresh urine by calcium hydroxide addition

Abstract: In this study, we investigated the prevention of enzymatic urea hydrolysis in fresh urine by increasing the pH with calcium hydroxide (Ca(OH)2) powder. The amount of Ca(OH)2 dissolving in fresh urine depends significantly on the composition of the urine. The different urine compositions used in our simulations showed that between 4.3 and 5.8 g Ca(OH)2 dissolved in 1 L of urine at 25 °C. At this temperature, the pH at saturation is 12.5 and is far above the pH of 11, which we identified as the upper limit for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 30 publications
2
120
2
Order By: Relevance
“…Etter et al [38] for instance reported challenges in making a profit out of struvite, at present only recovering 13% of the potential fertilizer value of urine. New techniques that do not use magnesium sulphate are being developed and could provide promising future avenues for urine valorization [39].…”
Section: Challenges To Profitabilitymentioning
confidence: 99%
“…Etter et al [38] for instance reported challenges in making a profit out of struvite, at present only recovering 13% of the potential fertilizer value of urine. New techniques that do not use magnesium sulphate are being developed and could provide promising future avenues for urine valorization [39].…”
Section: Challenges To Profitabilitymentioning
confidence: 99%
“…Other ways of preventing odour include stabilizing urine. Urea hydrolysis is the process by which carbon dioxide and free volatile ammonia are formed from urea (Randall et al, 2016). Pungent odours are expelled as a result of the urea hydrolysis process (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the addition of a Ca source is most likely not necessary, as Ca 2+ is an abundant ion in most waste streams [31,32]. It is worth mentioning that even when an external Ca source is required, the cost of dosing Ca is cheaper than dosing Mg [33,34]. Moreover, as calcium phosphate is the key component of mined phosphate rock, it can be used directly as a raw material for the production of phosphorus fertilizer in the existing facilities [22,31].…”
Section: Calcium Phosphate Precipitationmentioning
confidence: 99%
“…CaP solids can form without adding Ca 2+ since there is often already sufficient Ca 2+ in water bodies [57]. Therefore, P recovery via CaP formation and precipitation is a preferred method and has received a lot of attention [33,56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation